Modification of Tomato Planting Media to Improve the Quality of Farming Urban Vegetables - Wanti Mindari; Widi Wurjani; Purnomo Edi Sasongko (Jurnal Peduli Masyarakat, 2020)
The Women's Farmer Group, the PKK RT 03, RW 08 Rewwin, Waru, Sidoarjo group has carried out urban farming during the Covid 19 pandemic, but only some residents understand urban farming. The objectives of the activity are: 1) to increase the knowledge and skills of residents in farming turbans, (2) modification of media and irrigation arrangements, 3). Diversification of plant species cultivated to meet the needs of urban communities. Modification of planting media from various material sources as alternative planting. The method of implementation is through socialization and assistance in planting practices to harvest various kinds of vegetables and plant arrangements. The results of the activity show that the residents have been educated and the lifestyle in the agricultural turban has changed. Planting media from a mixture of soil and non-soil (compost, husk, cocopit, manure). The composition of the media mix that will support planting. The composition of the media for young and mature plants is different. The provision of water through drip irrigation is designed 2 times per day, namely in the morning and evening so that it is maintained and efficient. NPK fertilizer is given as basic fertilizer and a follow-up of 20 g / plant is given 4 times. The results of the demonstration plot for growing tomatoes at a pot capacity of 5 kg showed that the mixture of soil media + compost + husk + manure gave the highest and best yield of tomato fruit compared to the media mixture that was not as complete as the material.